Hubungan Interdialytic Weight Gain (IDWG) Score dan Kepatuhan Dietary Restriction dengan Gejala Restless Legs Syndrome pada Pasien Hemodialisa - Novia Karmiyati (Consilium Sanitatis: Journal of Health Science and Policy, 2023)
Objective: This study aims to analyze and determine the relationship between the Intradialytic Weight Gain (IDWG) value and adherence to dietary restrictions on the occurrence of Restless Legs Syndrome in patients undergoing hemodialysis at the HD Clinic Apotik Berkat Pangkal Pinang in 2020.Methods: This research is a descriptive analytic study with a cross sectional approach. This study involved 28 hemodialysis patients at the HD Clinic Apotik Berkat Pangkal Pinang as respondents. Results: The study results with the Chi-Square analysis obtained a p-value for IDWG was 0.006, and a p-value of 0.030 for dietary restrictions. Patients adhering to dietary restrictions would minimize the increase in IDWG values and reduce the impact of RLS. Suggestions that could be given based on this study were expected to improve compliance with dietary and fluid restrictions in HD patients so that complaints of RLS were reduced. Conclusion: This study ultimately concluded that there was a relationship between IDWG scores and dietary restriction compliance with the occurrence of RLS.